1992
DOI: 10.1038/jcbfm.1992.113
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Requirements for Accurate Measurements of Brain and Body Temperature during Global Forebrain Ischemia of Rat

Abstract: Summary:The methodological requirements for accurate measurements of brain and body temperature during brain ischemia have been validated in Wistar rats submit ted to 30 min of four-vessel occlusion. During ischemia, brains were exposed to three different temperature pro files: spontaneous cooling from 36 to 31°C (n = 10), con stant hypothermia at 30°C (n = 19), and constant normo thermia at 36°C (n = 21). Direct and indirect brain tem perature recordings were carried out by placing fine thermocouples (200 !-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 16 publications
(10 reference statements)
1
20
0
Order By: Relevance
“…Temperature difference in the superficial brain tissue can be up to 20 °C, so that the cerebral cooling is not uniform. This agrees well with the experimental observation that large temperature variations exist in the brain tissue (KULUZ et el., 1992;MIYAZAWA and HOSSMANN, 1992). Our theoretical simulation also predicts that the thickness of the brain tissue layer with temperature variations was approximately 17 mm in both adults and infants, it agrees well with the direct intraoperative measurements showing that the brain tissue temperature is essentially the same at 20 mm beneath the cortical surface (STONE et el., 1997).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Temperature difference in the superficial brain tissue can be up to 20 °C, so that the cerebral cooling is not uniform. This agrees well with the experimental observation that large temperature variations exist in the brain tissue (KULUZ et el., 1992;MIYAZAWA and HOSSMANN, 1992). Our theoretical simulation also predicts that the thickness of the brain tissue layer with temperature variations was approximately 17 mm in both adults and infants, it agrees well with the direct intraoperative measurements showing that the brain tissue temperature is essentially the same at 20 mm beneath the cortical surface (STONE et el., 1997).…”
Section: Discussionsupporting
confidence: 85%
“…During surface cooling, ambient or brain surface temperature will produce an artifact in the brain temperature measurement if the probe is placed in the superficial region. Furthermore, it has been shown that the temporal muscle temperature underestimated brain temperature by as much as 4 °C during global forebrain ischaemia of rats (KULUZ et al, 1992;MIYAZAWA and HOSSMANN, 1992). Temporal and spatial temperature gradients in the brain during hypothermia depend on heat convection due to blood flow, heat conduction through the tissue and metabolic heat generation in the heat balance.…”
mentioning
confidence: 98%
“…For rat brain Miyazawa and Hossman [33] report that 15 min after occlusion of all cerebral arteries temperature declines 3-4°C. This drop of temperature induces ADC reduction of 30×10 -8 cm 2 /s to 40×10 -8 cm 2 /s [33]. Nevertheless reduction of ADC in the contralateral hemisphere in our study was significantly higher (100×10 -8 cm 2 /s).…”
Section: Discussionmentioning
confidence: 98%
“…Temperature was monitored continuously with a thermistor probe im planted in the temporalis muscle, a location that accu rately reflects intracerebral temperature (Busto et al, 1987). Although recent studies have demonstrated that indirect brain temperature measurements may underesti mate direct brain temperature under ischemic conditions (Miyazawa and Hossmann, 1992), we have previously demonstrated a strong correlation between temporalis muscle temperature and intracerebral temperature in this (nonischemic) fluid percussion injury model (Jiang et aI., 1991). All surgical procedures were performed under complete anesthesia induced by 2% isoflurane in a 2: 1 mixture of N20/02.…”
Section: Fluid Percussion Injury and Tissue Processingmentioning
confidence: 99%